Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Discover precise answers to your questions from a wide range of experts on our user-friendly Q&A platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
(A). The wavelength decreases by a factor of 3.
Introduction :
Hi ! We all know that all type of electromagnetic wave, will have the same velocity as the speed of light, because light is part of electromagnetic wave too. The value of it is 300,000 km/s or [tex] \sf{3 \times 10^8} [/tex] m/s. As a result of this constant property, the shorter the wavelength, the greater the value of the electromagnetic wave frequency. This relationship can also be expressed in this equation:
[tex] \boxed{\sf{\bold{c = \lambda \times f}}} [/tex]
With the following condition :
- c = the constant of the speed of light in a vacuum ≈ [tex] \sf{3 \times 10^{8} \: m/s} [/tex] m/s
- [tex] \sf{\lambda} [/tex] = wavelength (m)
- f = electromagnetic wave frequency (Hz)
Explanation
In this problem, we underline one concept, namely : "the shorter the wavelength, the greater the value of the electromagnetic wave frequency". In question, the frequency of the waveform will increase by a factor of 3 from the beginning. So, to keep this value constant, the wavelength should be reduced by a factor of 3 from the initial condition.
Proof
Assume that:
- c = c' = speed of the electromagnetic wave is always the same (constant).
- [tex] \sf{\lambda} [/tex] = initial wavelength = [tex] \sf{\lambda} [/tex]
- f = initial frequency = f
- f' = final frequency = 3f
Let we count :
- [tex] \sf{\lambda}' [/tex] = final wavelength = ... [tex] \sf{\lambda} [/tex]
Step by step :
[tex] \sf{c = c'} [/tex]
[tex] \sf{\lambda \times f = \lambda' \times f'} [/tex]
[tex] \sf{\cancel{\lambda} \times \cancel f = x \cancel{\lambda} \times 3 \cancel{f}} [/tex]
[tex] \sf{1 = 3x} [/tex]
[tex] \sf{x = \frac{1}{3}} [/tex] (Q.E.D)
Conclusion
So, if the frequency value is increased by a factor of 3 from its original, then the wavelength will decrease by a factor of 3 from the original.
See More
- An example of calculating the frequency of an electromagnetic wave https://brainly.com/question/26437116
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.